2022
DOI: 10.3390/foods11223719
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Tocopherol Contents of Walnut Seed Oils Produced in Different European Countries Analyzed by HPLC-UV: A Comparative Study on the Basis of Geographical Origin

Abstract: A rapid HPLC-UV method was developed for the determination of tocopherols in walnut seed oils. The method was validated and the LODs ranged between 0.15 and 0.30 mg/kg, while the LOQs were calculated over the range of 0.50 to 1.00 mg/kg. The accuracy values ranged between 90.8 and 97.1% for the within-day assay (n = 6) and between 90.4 and 95.8% for the between-day assay (n = 3 × 3), respectively. The precision of the method was evaluated and the RSD% values were lower than 6.1 and 8.2, respectively. Overall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Walnut oil also contains a great number of phytosterols (106.5 mg/100 g) than others seed oils [68]. Additionally, walnut oil has a high content of α-, β-, γ-, and δ-tocopherols (Vitamin E) and pantothenate [69].…”
Section: Walnut Oilmentioning
confidence: 99%
“…Walnut oil also contains a great number of phytosterols (106.5 mg/100 g) than others seed oils [68]. Additionally, walnut oil has a high content of α-, β-, γ-, and δ-tocopherols (Vitamin E) and pantothenate [69].…”
Section: Walnut Oilmentioning
confidence: 99%
“…Tocopherols (α-, β-, γ-, and δ-) are part of the commonly known vitamin E complex, along with the corresponding tocotrienols, which protect against the non-enzymatic peroxidation of polyunsaturated fatty acids, are lipid-soluble, and can be found in high-fat plant foods, such as walnuts. In the first paper, Mitsikaris et al [1] determined the levels of tocopherols in walnut seed oils by HPLC-UV. The levels of the samples varied from four European countries and showed that the Ukrainian walnut seed oils exhibited significantly higher total concentrations.…”
mentioning
confidence: 99%